Efektivitas Penerapan Undang-Undang No. 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga Dalam Masalah Perceraian Di Indonesia: (Studi Kasus Putusan PN Tuban Nomor 179/Pid.Sus/2022/Pn Tbn) - Fadhli, Muhammad Rois (International Forum of Researchers and Lecturers, 2023)
. Indonesia is a state based on law whose administration of government power is based on law not power, the law is certainly used as a tool to fulfill the balance between Indonesian people in interacting, one of which is for the sake of achieving balance in the household. In the household, it has also been regulated regarding the elimination of domestic violence, namely Law No. 23 of 2004. In conducting this research, the researcher uses a deductive method of thinking research and raises two main issues what are the factors that cause violence in the household and how is the effectiveness of the application of Law Number 23 of 2004 concerning the elimination of domestic violence in divorce issues in Indonesia.